Islamic Republic of Iran : An Agricultural Policy Note - World Bank (Washington, DC, 2013)
This report addresses key structural, institutional, and sectoral policy impediments to achieving a higher, and sustained economic growth in the sector, and poverty reduction in rural areas of Iran. It focuses mainly on an assessment of agricultural development outcomes, a discussion of the agricultural policy agenda, and provides recommendations for future policy dialogue between the Bank, and the Government of Iran. On examining development outcomes, the report assesses the agricultural sector's contribution, which - though in decline - has displayed rapid growth (4.9 percent) during the course of the 1990's; identifies the strong rural content of poverty in Iran, where the proportion of the rural population living in households with income below the poverty line, is the highest; and, examines the increasing pressures on the natural resources, with deforestation and erosion reaching alarming proportions. Policy in the sector has been driven largely by the need to rely on domestic production, to meet the needs of a rapidly increasing demand. However, and despite significant rural development achievements, an inadequate market structure, and organization for commodity markets, land fragmentation, and related social issues, are hindering further development in agriculture and rural areas. Iran's agricultural exports face several constraints that arise from conflicting domestic policies relating to production, storage, distribution, food security, and pricing concerns. In the short-term, the Bank could provide input into the development of a Strategic Framework for Sustainable Agricultural and Rural Development, in the form of high impact focused technical studies, following the approach used with the energy subsidies. This could lead eventually to a comprehensive, and participatory Agricultural and Rural Development Strategy Note. Knowledge sharing with the private, and public sector requiring first in-depth studies, could be provided before putting in place a series of show-case projects, to transfer international best-practices in areas such as, marketing, land reform, or human development.